APLIKASI DOKUMENTASI AKREDITASI PROGRAM STUDI TEKNIK INFORMATIKA UNIVERSITAS JABAL GHAFUR BERBASIS FRAMEWORK CODEIGNITER - Nurul Rahmi (Yayasan Sagita Akademia Maju, 2024)
This study aims to develop an accreditation documentation application for the informatics engineering study program at Jabal Ghafur University using the CodeIgniter framework. This application was built to simplify the process of documenting and tracking accreditation requirements that must be met by the informatics engineering study program at Jabal Ghafur University. This study uses a web-based information system development method, starting with user needs analysis, system design, implementation, testing, and evaluation. This application is equipped with features such as user and accreditation team data management, accreditation criteria data management, and accreditation documentation data management for informatics engineering study programs. The test results show that this application can help simplify the accreditation process for the informatics engineering study program at Jabal Ghafur University. This application can also make it easier to track the accreditation requirements that must be met by the informatics engineering study program at Jabal Ghafur University.